Pounding the ground for the thunder god: Sounding platforms in the Prehispanic Andes (CE 1000–1532) - Lane, Kevin John (Elsevier, 2023)
The past is silent, or mostly so, yet sound can open a window to this same past. Early Spanish colonial ethnohistoric sources from the Andes are littered with references to indigenous dancing and music as an accompaniment to ritual and feasts. Recent archaeological research in the upper Ica Drainage on the late Prehispanic (CE 1000–1532) site of Viejo Sangayaico has revealed an open-air platform potentially prepared as a type of sprung or ‘sounding’ dancefloor which produces a deep percussion-like sound when stepped upon. I interpret this feature as a sounding platform for stomp dancing. The larger site's association to veneration of Andean lightning and thunder deity suggests that dancing at this location might have been in part attuned to this supernatural entity. Wider ethnohistoric evidence provide a potential parallel into understanding what type of activities were practiced on this platform and site.